Dicer Cleavage by Calpain Determines Platelet microRNA Levels and Function in Diabetes. Issue 2 (3rd July 2015) - Elgheznawy, Amro; Shi, Lei; Hu, Jiong; Wittig, Ilka; Laban, Hebatullah; Pircher, Joachim; Mann, Alexander; Provost, Patrick; Randriamboavonjy, Voahanginirina; Fleming, Ingrid
Abstract : Rationale: : MicroRNAs (miRNAs) are short noncoding RNA species generated by the processing of longer precursors by the ribonucleases Drosha and Dicer. Platelets contain large amounts of miRNA that are altered by disease, in particular diabetes mellitus. Objective: : This study determined why platelet miRNA levels are attenuated in diabetic individuals and how decreased levels of the platelet-enriched miRNA, miR-223, affect platelet function. Methods and Results: : Dicer levels were altered in platelets from diabetic mice and patients, a change that could be attributed to the cleavage of the enzyme by calpain, resulting in loss of function. Diabetes mellitus in human subjects as well as in mice resulted in decreased levels of platelet miR-142, miR-143, miR-155, and miR-223. Focusing on only 1 of these miRNAs, miR-223 deletion in mice resulted in modestly enhanced platelet aggregation, the formation of large thrombi and delayed clot retraction compared with wild-type littermates. A similar dysregulation was detected in platelets from diabetic patients. Proteomic analysis of platelets from miR-223 knockout mice revealed increased levels of several proteins, including kindlin-3 and coagulation factor XIII-A. Whereas, kindlin-3 was indirectly regulated by miR-223, factor XIII was a direct target and both proteins were also altered in diabetic platelets. Treating diabetic mice with a calpain inhibitor prevented loss of platelet dicer as well as the diabetes mellitus–induced decrease in platelet miRNA levels and the upregulation of miR-223 target proteins. Conclusions: : Thus, calpain inhibition may be one means of normalizing platelet miRNA processing as well as platelet function in diabetes mellitus. Abstract : Supplemental Digital Content is available in the text.